Factors Influencing Information Seeking Behaviour for Halal Food Products Among Malaysian Muslim Consumers: A Conceptual Framework - S. Omari, F.; Azman, N.; Ismail, R. (Universiti Sains Islam Malaysia, 2024)
Non-Indexed Publication